2013
DOI: 10.1002/jrs.4376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al content on the structure of Al‐substituted goethite: a micro‐Raman spectroscopic study

Abstract: The characterization of X-ray diffraction, X-ray fluorescence, and field emission scanning electron microscope were used to confirm the successful preparation of Al-substituted goethite with different Al content. The micro-Raman spectroscopy was utilized to investigate the effect of Al content on the goethite lattice. The results show that all the feature bands of goethite shifted to high wavenumbers after the occurrence of Al substitution for Fe in the structure of goethite. The shift of wavenumber shows a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 60 publications
4
19
0
Order By: Relevance
“…Analyzing the characteristic peaks of each phase, it can be concluded that magnetite phase occurs in the samples Mag-01 to Mag-04 (Figure 3a) and magnetite and maghemite phases occur in the samples Mag-05 and Mag-06 (Figure 3b). There is good agreement in the reported spectra of goethite [17][18][19] with bands at 92, 164, 203, 243, 297, 384, 478, 546 and 663 cm -1 found in some regions of sample Mag-01 (Figure 3c). Table 2 shows the evaluated synthesis parameters and the obtained crystallite size and crystallinity values for all samples, estimated by Scherrer equation.…”
Section: Powder Characterizationsupporting
confidence: 85%
“…Analyzing the characteristic peaks of each phase, it can be concluded that magnetite phase occurs in the samples Mag-01 to Mag-04 (Figure 3a) and magnetite and maghemite phases occur in the samples Mag-05 and Mag-06 (Figure 3b). There is good agreement in the reported spectra of goethite [17][18][19] with bands at 92, 164, 203, 243, 297, 384, 478, 546 and 663 cm -1 found in some regions of sample Mag-01 (Figure 3c). Table 2 shows the evaluated synthesis parameters and the obtained crystallite size and crystallinity values for all samples, estimated by Scherrer equation.…”
Section: Powder Characterizationsupporting
confidence: 85%
“…The reflections of goethite disappeared and were replaced by those of hematite, indicating that the goethite was transformed into hematite when the thermal treatment temperature was more than 400°C. The decomposition of goethite, which occurs at more than 225°C, has been was previously reported (Rendon et al, 1983;Serna and Iglesias, 1986;Liu et al, 2013b). However, the intensity of the hematite reflections increased as the thermal treatment temperature increased, and well-defined hematite was obtained after thermal treatment at 800°C.…”
Section: Xrdmentioning
confidence: 53%
“…Some structural conclusions concerning particular minerals, like solid‐state form or average crystallite size, were also drawn from the measured spectra . Liu and coworkers studied the effect of Al content on the structure of Al‐substituted goethite using micro‐Raman spectroscopy . Noguchi and coworkers used micro‐Raman and photoluminescence spectroscopies to image the internal stress around a mineral inclusion in a sapphire crystal.…”
Section: Introductionmentioning
confidence: 56%
“…[194] Liu and coworkers studied the effect of Al content on the structure of Al-substituted goethite using micro-Raman spectroscopy. [195] Noguchi and coworkers used micro-Raman and photoluminescence spectroscopies to image the internal stress around a mineral inclusion in a sapphire crystal. In general, internal stress fields induced by mineral inclusions reflect the pressure and temperature conditions at which the host sapphire gemstones were crystallized.…”
Section: Single Crystalsmentioning
confidence: 99%